(untitled) (La U Investiga, 2024)
The somatotype is influenced by bone structure, metabolism, the amount of muscle mass and fat mass, to classify the shape of the human body into ectomorph, endomorph and mesomorph or mixture between them. The general objective of this study was to evaluate the nutritional status and somatotype of the students of the Nutrition career of the Universidad Técnica del Norte in the academic period September - March 2020. And the specific objective was to orient this group of women to classify their sports discipline according to their somatotype. A descriptive, retrospective and cross-sectional research was carried out. A total of 67 women from first to fifth semester of the Nutrition career were evaluated, the exclusion criteria were pregnant and breastfeeding women. As results it was found that the predominant somatotype was the Endomorph with 79.10% followed by the Endo mesomorph with 16.42%, then the Ecto endomorph with 2.99% and the least relevant was the endo ectomorph with 1.49%. Regarding nutritional status, 62.69% were found to be normal, 13.43% of the sample was overweight l, 13.43% was overweight ll, 5.97% was obese and only 4.48% was underweight. In conclusion, the female students of the Nutrition career present a predominance of the Endomorphic somatotype, for which they have greater ability in sports of strength, power, and strength training.